Anemia and micronutrient status of women of childbearing age and children 6–59 months in the Democratic Republic of the Congo - Harvey-Leeson, Sarah; Karakochuk, Crystal D.; Hawes, Meaghan; Tugirimana, Pierrot L.; Bahizire, Esto; Akilimali, Pierre Z.; Michaux, Kristina D.; Lynd, Larry D.; Whitfield, Kyly C.; Moursi, Mourad; Boy, Erick; Foley, Jennifer; et al. (MDPI, 2016)
Little is known about the micronutrient status of women and children in the Democratic Republic of the Congo, which is critical for the design of effective nutrition interventions. We recruited 744 mother-child pairs from South Kivu (SK) and Kongo Central (KC). We determined hemoglobin (Hb), serum zinc, vitamin B12, folate, ferritin, soluble transferrin receptor (sTfR), retinol binding protein (RBP), C-reactive protein, and α-1 acid glycoprotein concentrations. Anemia prevalence was determined using Hb adjusted for altitude alone and Hb adjusted for both altitude and ethnicity. Anemia prevalence was lower after Hb adjustment for altitude and ethnicity, compared to only altitude, among women (6% vs. 17% in SK; 10% vs. 32% in KC), children 6–23 months (26% vs. 59% in SK; 25% vs. 42% in KC), and children 24–59 months (14% vs. 35% in SK; 23% vs. 44% in KC), respectively. Iron deficiency was seemingly higher with sTfR as compared to inflammation-adjusted ferritin among women (18% vs. 4% in SK; 21% vs. 5% in KC), children 6–23 months (51% vs. 14% in SK; 74% vs. 10% in KC), and children 24–59 months (23% vs. 4% in SK; 58% vs. 1% in KC). Regardless of indicator, iron deficiency anemia (IDA) never exceeded 3% in women. In children, IDA reached almost 20% when sTfR was used but was only 10% with ferritin. Folate, B12, and vitamin A (RBP) deficiencies were all very low (<5%); RBP was 10% in children. The prevalence of anemia was unexpectedly low. Inflammation-adjusted zinc deficiency was high among women (52% in SK; 58% in KC), children 6–23 months (23% in SK; 20% in KC), and children 24–59 months (25% in SK; 27% in KC). The rate of biochemical zinc deficiency among Congolese women and children requires attention.